Tanggung Jawab Notaris dalam Pembuatan Akta Perusahaan dan Implikasinya terhadap Perbuatan Pidana Pemalsuan Dokumen : (Studi Atas Putusan Nomor 589/Pid.B/2023/PN Jkt.Sel) - Djajaputra, Gunawan; Albert (Universitas Muhammadiyah Ponorogo, 2025)
Notaries play a strategic role in the Indonesian legal system, particularly in the preparation of company deeds of establishment and amendments. A notary's responsibilities extend beyond administrative duties and include preventive legal functions and oversight of document validity. The primary duties of a notary include verifying the identity of the parties, verifying the authority of the management, verifying the authenticity of documents, recording, storing, and providing legal advice to prevent misuse of documents by unauthorized parties. The case of Muhammad Rinaldi in Decision Number 589/Pid.B/2023/PN Jkt.Sel emphasizes the importance of verifying and legalizing amendments, as illegal use of old deeds can result in legal, financial, and reputational losses for both the company and third parties. Notarial deeds have full evidentiary power as stipulated in Article 1868 of the Civil Code and Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (UUJN). However, unlawful misuse of notarial deeds can be classified as a criminal act of document forgery as referred to in Article 263 paragraph (2) of the Criminal Code. Legal protection for third parties acting in good faith is still guaranteed, including the right to restitution for losses resulting from forgery. This study confirms that integrity, professionalism, and the implementation of strict verification procedures by notaries are essential factors in ensuring legal certainty, preventing misuse of deeds, and protecting the rights of all interested parties. Thus, the role of notaries must be understood not only as the maker of deeds, but also as the guardian of legality and guardian of legal morality in notarial practice in Indonesia.